Ash fertilization increases long-term timber production in drained nitrogen-poor Scots pine peatlands - Hökkä, Hannu; Ahtikoski, Anssi; Sarkkola, Sakari; Väänänen, Päivi (National Research Council Canada, 2024)
Wood ash fertilization remarkably increases tree growth and hence, carbon sequestration in drained boreal peatland forests, particularly in nitrogen (N)-rich Scots pine sites with limited phosphorus (P) and potassium (K). Because ash lacks N, Ndeficient ombrotrophic and poor oligotrophic sites are generally considered unsuitable for ash fertilization. In this study, timber production was investigated in six field experiments in N-poor, drained Scots pine dominated peatlands in central Finland, where ash fertilization was applied 15–85 years earlier. Ash significantly increased tree growth in all the study sites. Unfertilized plots showed long-term average mean annual increment (MAI) of 2.01 m3·ha−1·a−1, whereas in fertilized plots MAI was 4.46 m3·ha−1·a−1. An analysis with nonlinear mixed effects model revealed a faster volume yield development and higher asymptote of the mean curve in fertilized plots. Higher amount of K in the ash significantly increased the response. Fertilizations were financially lucrative: on average, the break-even cost surpassed the ash fertilization cost (390 € ha−1) more than two-fold at 5% interest rate. The current nutrient status of fertilized trees was rather balanced. The results proved that the long-term growth response to ash fertilization in poor drained peatland sites is comparable to N-rich sites, but the response time is distinctively longer.
Keywords: profitability; ash fertilization; drainage; peatlands; volume yield; Pinus sylvestris